Improving infrastructure resilience. Issue 1 (2nd January 2019) - Elms, David; McCahon, Ian; Dewhirst, Rob
ABSTRACT: Most formal engineering approaches to uncertainty use risk-based methods. Because risk formulations have a number of limitations there are situations where a resilience approach is preferable. A problem with resilience is the difficulty of measuring it. The paper discusses the issue and shows how a resilience formulation was used to prioritise actions to improve infrastructure resilience in an extensive region of New Zealand. The region was a complex system-of-systems so a systems approach was used. Once modelled, the infrastructure system was probed using three natural-hazard scenarios to determine system-element vulnerabilities. The vulnerability of each element was then matched with an importance value reflecting the effect of an element failure on community resilience. Community resilience was quantified in terms of overall income coming from three main sources each of which could be characterised by flow in a virtual pipeline. The pipelines were complex: tourism, for instance, required not only roads but also accommodation, communication, access and so on. The effect of infrastructure failures on pipeline flow and hence income quantified the relative importance of each infrastructure element. The vulnerability and importance values as a pair prioritised resilience-improving intervention for the element.